Hubungan Intensitas Menonton Youtube Beauty Vlogger dan Persepsi Mengenai Kredibilitas Beauty Vlogger dengan Perilaku menggunakan Makeup oleh Remaja - Asri Aulia Rachmawati; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Makeup trends in Indonesia are developing through beauty vlogger content, which is mostly watched by teenagers. Teenagers tend to always follow the latest makeup trends to look beautiful. This is done because teenagers want to be like what the model they see, both the style of makeup and using various beauty products. Teen makeup behavior was allegedly a result of several factors such as the intensity of watching beauty vloggers on YouTube and one's perception of the credibility of beauty vloggers. This research aims to explain the intesity relationship of wathcing youtube beauty vlogger and perception regarding the credibility of the beauty vlogger with the behavior of using makeup by teenegers. The theory used is social learning theory and source credibility theory. The sample technique this research is using the non probability sampling with purposive sampling method. The number of sample is 60 people with criteria of female adolencests aged 13-18 years, watching the beauty vlogger and domiciled in the city of Semarang. The data analysis is using Pearson’s Correlation. The first hypothesis testing result showed there is no correlation between the intensity of wathcing youtube beauty vlogger with the behavior of using makeup by teenagers, with significance value of 0,404. The second hypothesis testing result showed there is correlation between perception on the credibility of the beauty vlogger with the behavior of using makeup by teenagers, with a value 0,002 of significance and 0,396 of correlation coefficient. With this result, further research is recommended using other variables, such as peergroup communication intensity or social status variables. Teen audiences are also expected to filter and be selective with all the information conveyed by beauty vloggers regarding the use of makeup.